2008
DOI: 10.1094/mpmi-21-7-0947
|View full text |Cite
|
Sign up to set email alerts
|

The Outer Membrane Protein TolC from Sinorhizobium meliloti Affects Protein Secretion, Polysaccharide Biosynthesis, Antimicrobial Resistance, and Symbiosis

Abstract: Sinorhizobium meliloti is capable of establishing a symbiotic nitrogen fixation relationship with Medicago sativa. During this process, it must cope with diverse environments and has evolved different types of transport systems that help its propagation in the plant roots. TolC protein family members are the outer-membrane components of several transport systems involved in the export of diverse molecules, playing an important role in bacterial survival. In this work, we have characterized the protein TolC fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 55 publications
6
41
0
1
Order By: Relevance
“…Deletions of the two RNDtype pumps, SMc01094-SMc01095 (smeCD) or SMc01828-SMc01829 (smeEF), in a ⌬smeAB background resulted in a further increase in susceptibility to chloramphenicol and nali- dixic acid or to erythromycin and tetracycline, respectively (Table 2; see also Table S3 in the supplemental material). Consistent with the findings of Cosme et al (8), deletion of the tolC gene resulted in increased susceptibility to antibiotics, detergents, dyes, and plant-derived chemicals (Table 2). Deletions in the remaining two OMF genes, SMa1037 and SMc02281, had no effect on antimicrobial susceptibility in both wild-type and ⌬tolC backgrounds (see Table S3 in the supplemental material), indicating that the SMa1037 and SMc02281 proteins are not involved in the efflux of toxic substances tested.…”
Section: Identification Of Multicomponent-type Mdr Pump Genessupporting
confidence: 89%
See 2 more Smart Citations
“…Deletions of the two RNDtype pumps, SMc01094-SMc01095 (smeCD) or SMc01828-SMc01829 (smeEF), in a ⌬smeAB background resulted in a further increase in susceptibility to chloramphenicol and nali- dixic acid or to erythromycin and tetracycline, respectively (Table 2; see also Table S3 in the supplemental material). Consistent with the findings of Cosme et al (8), deletion of the tolC gene resulted in increased susceptibility to antibiotics, detergents, dyes, and plant-derived chemicals (Table 2). Deletions in the remaining two OMF genes, SMa1037 and SMc02281, had no effect on antimicrobial susceptibility in both wild-type and ⌬tolC backgrounds (see Table S3 in the supplemental material), indicating that the SMa1037 and SMc02281 proteins are not involved in the efflux of toxic substances tested.…”
Section: Identification Of Multicomponent-type Mdr Pump Genessupporting
confidence: 89%
“…The MFP genes were located adjacent to all of the RND genes. A computational search for the OMF family proteins of S. meliloti identified SMc02082 (designated TolC) (8). This study also identified two sequences, designated SMc1037 and SMc02281, encoding the outer membrane efflux protein motif (Pfam ID PF02321), but these sequences were not analyzed because they displayed low similarity to E. coli TolC and each had a possible lipid attachment site, unlike TolC (8).…”
Section: Identification Of Multicomponent-type Mdr Pump Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased diameter (from 13.5 to 29.0 Å) upon TolC-AcrA association, would admit the translocation of larger molecules, which is in agreement with other strong and recent experimental evidences. [17][18][19] The new proposed model also satisfied the Cryo-EM map volume described by Du et al 6 as seen in Figure 4c. Torres et al 2385 Vol.…”
Section: Resultssupporting
confidence: 70%
“…The complete channel exports virulence-associated proteins, antibiotics, detergents, colicin V, and organic solvents (67). The TolC protein plays an important role in the virulence of many Gram-negative bacterial pathogens (7,11,13,22,32,46). Thus, TolC should not be overlooked for its possible role in protein secretion in rickettsiae.…”
mentioning
confidence: 99%